Kritisk diakonal literacy: Om profesjonell yrkesutøvelse, kompetanse og samhandling (Nordic Journal of Practical Theology, 2026)
Diaconia requires collaboration across structures and institutions, and diaconal tasks involve several professions. Professionals contribute with their own expertise but are also dependent on understanding the identity and self-understanding of collaborating partners. This article therefore asks: What kind of diaconal competence do professionals such as social workers, nurses and child welfare professionals etc. need in interaction with diaconal actors? I begin by explaining how key diaconal actors present their own diaconal identity. Attention is then drawn to the diaconal competence that such organizations partly expect, and partly want, from professionals within or outside their own institutional framework. This leads to a discussion of the concept of literacy and its associated critical perspective, and I argue that professional practitioners need critical diaconal literacy in their encounters with diaconal actors. The discussion is rounded off with a discussion of the implications this has for professional education.
Keywords: Profession; Diakonia; Diaconia; Literacy; Inner city mission; Norwegian Church Aid; Criticism; Cooperation